Perancangan Buku Interaktif Digital Edukasi Rambu Untuk Anak Usia Dini - Iqbal Maimun Umar; Joni Nur Budi Kawulur (ULTIMART Jurnal Komunikasi Visual, 2022)
In suppressing the high rate of road accidents, the United Nations and related institutions implement the Road Safety to Zero Accident campaign, by running the Decade of Action for Road Safety program in two periods 2011-2020 and 2021-2030. which targets less than 50% of traffic deaths and injuries by 2030. Indonesia also launched the campaign program by conducting the Road Safety Campaign. To support the campaign, various ways were carried out, including educating an early age on the introduction of traffic signs, including in PAUD, Traffic Education Park, or from TV, radio, video, social media, games, animation, augmented reality and others. In this study, the author designed a digital interactive book for traffic sign education aimed at ages 3-6 years. The research method includes qualitative and quantitative, consisting of primary data interviews with the DKI Transportation Agency, and the head of the Bike To Work community, one of the bicycle communities as road users. The author observes the Cibubur traffic park to find out the traffic order learning facilities. We also conducted a survey of signs during a pandemic in the nearest neighborhood, Jl. Transyogi Cibubur. As a complement to our method, we distributed questionnaires to children who were guided by their parents in filling out. Secondary data from internet sources resulting from the accident rate survey, as well as visual references as another point of view for designing digital books. Keywords: education; signs; traffic; books; interactive; digital